1987
DOI: 10.1113/jphysiol.1987.sp016616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive activity on developed force and intracellular sodium in isolated sheep and dog Purkinje fibres.

Abstract: SUMMARY1. When cardiac muscle is stimulated after a rest there is a gradual increase in force development over several minutes. The origin of this 'force staircase' was investigated in experiments on sheep and dog Purkinje fibres. Particular attention was paid to the possible role of changes in the intracellular Na+ activity (aNa).2. The first line of evidence for a role for aka came from a comparison of sheep and dog Purkinje fibres generating action potentials: after a change in the stimulus rate the slow ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 37 publications
6
30
0
Order By: Relevance
“…When the external stimulus is switched off, there is a period of quiescence before stable automaticity resumes ( figure 4c(i)). The characteristics of the simulated overdrive suppression are similar to the experimental observations by Boyett et al (1987).…”
Section: (A ) Simulated Action Potential Of Human Purkinje Fibre Cellssupporting
confidence: 82%
“…When the external stimulus is switched off, there is a period of quiescence before stable automaticity resumes ( figure 4c(i)). The characteristics of the simulated overdrive suppression are similar to the experimental observations by Boyett et al (1987).…”
Section: (A ) Simulated Action Potential Of Human Purkinje Fibre Cellssupporting
confidence: 82%
“…In contrast, Lederer & Sheu (1983) suggested that the progressive increase in twitch tension during the staircase in sheep Purkinje fibres was the result of the accompanying rise in aNa, because the two changes occurred over a similar time course. Evidence to support this hypothesis was obtained by Boyett et al (1987b): for example, in voltage clamped sheep Purkinje fibres they observed that tetrodotoxin decreased both the rise in a'a and the progressive increase in twitch tension during the staircase. Evidence that a'a may also be involved in the staircase in ventricular muscle was obtained by Seibel (1986): for example, he observed that tetrodotoxin decreased the progressive increase in twitch tension during the staircase in guinea-pig ventricular muscle.…”
Section: Discussion Ana In Ventricular Myocytessupporting
confidence: 49%
“…In rat ventricular myocytes aia increased by 0-78 mm Hz-'. A similar rate-dependent increase in a'a (measured using Na+-sensitive microelectrodes) has been observed in guinea-pig papillary muscle (Wang et al 1988), rat atrial muscle (Ruch, Kennedy & Seifen, 1988) and sheep and dog Purkinje fibres (Cohen et al 1982;Lederer & Sheu, 1983;Ellis, 1985;Abete & Vassalle, 1987Boyet, Hart & Levi, 1987 a;Boyett et al 1987b;Lee, Im & Sonn, 1987;Bountra, Kaila & Vaughan-Jones, 1988 a, b The similarity between the results obtained in the present study and those from studies in which a'a was determined with Na+-sensitive microelectrodes suggests that the SBFI fluorescence ratio is a reasonable measure of aNa.…”
Section: Discussion Ana In Ventricular Myocytesmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, the presence of a clear positive force staircase at 2 and 4 Hz indicates that a positive inotropic mechanism is more than compensating for the negative inotropic influence of the intracellular acidosis. Such a positive inotropic mechanism could be the rise in aia (Lederer & Sheu, 1983;Boyett et al 1987b; see page 358 which, like the fall in pHi, increases roughly linearly with frequency (Fig. 3).…”
Section: Effect Of Frequency On Phimentioning
confidence: 99%